Archie celebrates Diwali - Ruths, Mitali Banerjee (Charlesbridge, 2021)
"Archie is worried that her school friends won't like Diwali, her favorite Hindu holiday, and when a storm knocks out the electricity, it looks like the party may be ruined."--Provided by publisher.